2017
DOI: 10.1016/j.cortex.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Face inversion reveals holistic processing of peripheral faces

Abstract: Face perception is accomplished by face-selective neural processes, involving holistic processing that enables highly efficient integration of facial features into a whole-face representation. It has been shown that in face-selective regions of the ventral temporal cortex (VTC), neural resources involved in holistic processing are primarily dedicated to the central portion of the visual field. These findings raise the intriguing possibility that holistic processing might be the privilege of centrally presented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 77 publications
(127 reference statements)
10
13
0
Order By: Relevance
“…We interpret this as indicative of equivalent processing of spatial relations for RVF and LVF half-faces viewed in isolation. Previous studies using a face inversion manipulation have reported that holistic processing of spatial relations can occur for peripherally viewed faces in both hemifields (Kovács, Knakker, Hermann, Kovács, & Vidnyánszky, 2017), but is greater in the LVF than the RVF (Cattaneo et al, 2014;Hillger & Koenig, 1991;Leehey, Carey, Diamond, & Cahn, 1978). Our finding of equivalent processing for RVF and LVF halves of centrally viewed faces when viewed alone suggests that greater face-processing resources are available for centrally viewed faces as compared to peripherally viewed faces.…”
Section: Rh Superiority and Lvf Advantagessupporting
confidence: 44%
“…We interpret this as indicative of equivalent processing of spatial relations for RVF and LVF half-faces viewed in isolation. Previous studies using a face inversion manipulation have reported that holistic processing of spatial relations can occur for peripherally viewed faces in both hemifields (Kovács, Knakker, Hermann, Kovács, & Vidnyánszky, 2017), but is greater in the LVF than the RVF (Cattaneo et al, 2014;Hillger & Koenig, 1991;Leehey, Carey, Diamond, & Cahn, 1978). Our finding of equivalent processing for RVF and LVF halves of centrally viewed faces when viewed alone suggests that greater face-processing resources are available for centrally viewed faces as compared to peripherally viewed faces.…”
Section: Rh Superiority and Lvf Advantagessupporting
confidence: 44%
“…By manipulating face orientation in our first task, we thus hoped to examine the extent to which the FFDE is selective for faces, as opposed to being a reflection of more general properties of visual processing in the periphery. The lack of an effect of inversion in our task (despite evidence that other inversion effects are not limited to central vision 32,33 ) suggests that face-specific mechanisms at best make a relatively small contribution to the FFDE (see our discussion following Experiment 1 regarding the interpretation of Bayes Factors between 1–3). We therefore conjecture that the FFDE may depend primarily on general properties of object processing in the visual periphery, or lower-level mechanisms that apply to an even broader class of stimuli.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the present result is interesting in that only the right FFA showed the largest response to faces irrespective of the visual field. Similarly, Kovacs, Knakker, Hermann, Kovacs, and Vidnyanszky (2017) reported that the face‐N170 showed right hemispheric specialization without contralateral predominance, regardless of RVH or LVH. This is consistent with the right hemisphere being specialized for face recognition (Davies‐Thompson et al., 2016; Kanwisher, McDermott, et al, 1997).…”
Section: Discussionmentioning
confidence: 87%